Functional Analysis of Glycoprotein L (gL) from Rhesus Lymphocryptovirus in Epstein-Barr Virus-Mediated Cell Fusion Indicates a Direct Role of gL in gB-Induced Membrane Fusion - Plate, Aileen E. (American Society for Microbiology (ASM), 2009)
Glycoprotein L (gL), which complexes with gH, is a conserved herpesvirus protein that is essential for Epstein-Barr virus (EBV) entry into host cells. The gH/gL complex has a conserved role in entry among herpesviruses, yet the mechanism is not clear. To gain a better understanding of the role of gL in EBV-mediated fusion, chimeric proteins were made using rhesus lymphocryptovirus (Rh-LCV) gL (Rh gL), which shares a high sequence homology with EBV gL but does not complement EBV gL in mediating fusion with B cells. A reduction in fusion activity was observed with chimeric gL proteins that contained the amino terminus of Rh gL, although they retained their ability to process and transport gH/gL to the cell surface. Amino acids not conserved within this region in EBV gL when compared to Rh gL were further analyzed, with the results mapping residues 54 and 94 as being functionally important for EBV-mediated fusion. All chimeras and mutants displayed levels of cell surface expression similar to that of wild-type gL and interacted with gH and gp42. Our data also suggest that the role of gL involves the activation or recruitment of gB with the gH/gL complex, as we found that reduced fusion of Rh gL, EBV/Rh-LCV chimeras, and gL point mutants could be restored by replacing EBV gB with Rh gB. These observations demonstrate a distinction between the role of gL in the processing and trafficking of gH to the cell surface and a posttrafficking role in cell-cell fusion.